y+3=-11

Simple and best practice solution for y+3=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+3=-11 equation:


y+3=-11

We simplify the equation to the form, which is simple to understand
y+3=-11

We move all terms containing y to the left and all other terms to the right.
+1y=-11-3

We simplify left and right side of the equation.
+1y=-14

We divide both sides of the equation by 1 to get y.
y=-14

See similar equations:

| 12=7x+25 | | 12x+124=-32 | | 79=7x+12 | | 120-11x=-34 | | x+4-5x=3 | | 0.20s+0.32=520s | | (8y-7x)(8y+7x)= | | 0.18M+16=40.54M | | 12-7x=-6 | | -9-5x=-54 | | 10-3t=4 | | 0.2b+9=0.5b+18 | | 3x*6=39 | | -2v(v-5)(v-6)=0 | | 7x(8-2)= | | 11k-5=9k+7 | | 11-46=n | | -3(4y-4)=2(1-7y)+11 | | 2ln(x)=21 | | 3k-5-10k=23-1k | | -2x-2=-6-2 | | 5+2(4x-3)= | | 3x(x+4)-4=2(x+4)+x | | 19.03-12.9h=-14h | | 4x-7-3+2x=8 | | -(3y-6)+4(5y-8)=8 | | -13y+7+9=-10y-11 | | 9(x+3)-5x-3(5+3x)= | | 0.5n-18=-4 | | -q+17=-2q | | 17c-9=18c-19 | | c/8=41 |

Equations solver categories